Cow Farmer Household Consumption Pattern - Muhammad Thamrin; Dewa Putu Siantara; Liza Frisiliya Andriyana HRP (JASc (Journal of Agribusiness Sciences), 2020)
This research was conducted in Desa Sengon Sari Kecamatan Aek Kuasan Kabupaten Asahan, which aims to determine the consumption pattern of cattle breeders' households. The data analysis method used is descriptive analysis and multiple linear regression. The results showed that the percentage of total household consumption expenditure for food consumption was 44.38%, while consumption expenditure for non-food consumption was 55.62%. Multiple linear regression analysis shows that the variables of food expenditure, non-food expenditure and outside income from livestock farming have an effect on the household income of cattle breeders.